Development of a Realistic Mathematics Education-Based Teaching Module Integrated with Culture for Students at SMAN 1 Palopo - Fiki Waris; Taufiq Taufiq; Ma’rufi Ma’rufi; Patmaniar Patmaniar (Jurnal Studi Guru dan Pembelajaran, 2026)
The limited availability of teaching materials that connect mathematical concepts with students’ real-life and cultural contexts has become a critical challenge in improving students’ conceptual understanding and cultural awareness in mathematics learning. Therefore, this study aims to develop a culture-integrated teaching module based on the Realistic Mathematics Education approach for students at SMAN 1 Palopo, particularly on the topic of systems of linear equations in three variables. This study employed a research and development (R&D) method using the 4D (Define, Design, Develop, and Disseminate) development model. The research subjects consisted of students of SMAN 1 Palopo and mathematics teachers involved in the implementation stage. Data were collected using module validation sheets, learning implementation observation sheets, teacher response questionnaires, student response questionnaires, and learning outcome tests. The product analysis procedures included validity analysis by experts, practicality analysis based on teacher and student responses, and effectiveness analysis based on learning implementation and student learning outcomes. The results of the development analysis indicate that the Realistic Mathematics Education-based teaching module integrated with local culture is valid, practical, and effective. Expert validation results show that the module meets the language and presentation criteria. Teacher and student responses indicate positive perceptions of the module’s usability and relevance. Furthermore, learning outcome test results demonstrate that students were able to solve problems according to the indicators of Realistic Mathematics Education integrated with culture, indicating improved understanding of systems of linear equations in three variables.